PENGARUH HEALTH EDUCATION DENGAN MEDIA LEAFLET PADA REMAJA PUTRI DALAM DETEKSI DINI KANKER PAYUDARA MELALUI PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Devi Roliana; Redha Ulfa; Silvia Mariana; Rosa Riya (Jurnal Kesehatan dan Pembangunan, 2026)
Breast cancer is the most common type of cancer among women in Indonesia, with an incidence rate of 42.1 cases and a mortality rate of 17 deaths per 100,000 population, resulting in over 22,000 deaths (Indonesian Ministry of Health, 2022). This study aimed to examine the impact of health education using leaflets on adolescent girls regarding early breast cancer detection through breast self-examination (BSE). This quantitative study employed a one-group pretest-posttest design and was conducted at the AN-Nur Islamic Boarding School between January and February 2026. The study population comprised all adolescent girls at the AN-Nur Islamic Boarding School, totaling 85 individuals. A random sampling technique using Slovin's formula resulted in a sample of 46 respondents. The independent variables were knowledge and attitude, while the dependent variable was health education using leaflets. The results showed that the knowledge of adolescent girls at the AN-Nur Islamic Boarding School improved following the BSE health education, with the mean score rising from 1.33 to 2.78; their attitudes also improved, with the mean score increasing from 1.07 to 2.00. The study concludes that there was a significant impact on the knowledge and attitudes of the adolescent girls—based on the difference between pretest and posttest results—at the AN-Nur Islamic Boarding School, with a p-value of 0.001 (<0.05).